BUSINESS COMMUNICATION PATTERNS IN MARKET EVOLUTION THEORY AL-GHAZALI - Ahmad Afif (Indonesian Journal of Islamic Communication, 2021)
Some people may not think that the formation of a market is intertwined because of branched communication, even it was only through one-way communication at first, which is considered sufficient to be called a market through only one transaction. Moreover, understanding of market is only limited to the place and not understanding the substance of the market. The theory of market evolution of al ghazali is a prototype for the birth of the market, but it do not mention that the market is the place as today. The description of communication in theory needs to be understood in more depth, so that it can describe the advanced aspects of the pattern of business communication which is the benchmark. In addition, this communication has a pattern that will eventually shape the next new markets. This research is descriptive qualitative that observes the symptoms and phenomena that occur around al-Ghazali's theory of market evolution from the aspect of business communication, so that it produces an equivalent term, namely communication needs. This research produces three possible formulations, namely finding patterns of business communication which are the basis for the birth of advanced aspects, business communication patterns in al-Ghazali's theory of market evolution have the nature of a Need Communication Link (communication needs channel). The next aspects are communication needs and communication segmentation. Both are born simultaneously, but they have different domains. Communication needs gave birth to new market branches. In other words, if there is a need, then there must be communication, either new needs with new communications or something else. It is called by communication needs at the next level which create other new needs. Whereas segmentation communication creates significant and profitable objects from business lines that run through the supply and demand base, even under certain conditions it creates its own demand, at a certain time and place.